2020
DOI: 10.1111/trf.16102
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic testing in oncology patients (including for the diagnosis of fibrinolysis): Review of existing evidence, technology comparison, and clinical utility

Abstract: The quantification of the coagulopathic state associated with oncologic and hematologic diseases is imperfectly assessed by common coagulation tests such as prothrombin time, activated partial thromboplastin time, fibrinogen levels, and platelet count. These tests provide a static representation of a component of hemostatic integrity, presenting an incomplete picture of coagulation in these patients. Viscoelastic tests (VETs), such as rotational thromboelastometry (ROTEM) and thromboelastography (TEG), as whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 116 publications
0
19
0
Order By: Relevance
“…The risk of a clinically significant VTE is four-to-seven times higher in oncologic patients compared to the general population [ 20 ]. Many causes such as malignancy-induced platelet activation have been implicated in cancer-associated thrombosis while various factors related to surgery, such as endothelial damage and massive release of tissue factor, also add to the overall increased thrombotic risk [ 21 , 22 ]. Further understanding the hemostatic derangements that result in the prothrombotic state of surgical oncologic patients may allow for the development of targeted thrombophylactic measures focused on specific aspects of the hemostatic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of a clinically significant VTE is four-to-seven times higher in oncologic patients compared to the general population [ 20 ]. Many causes such as malignancy-induced platelet activation have been implicated in cancer-associated thrombosis while various factors related to surgery, such as endothelial damage and massive release of tissue factor, also add to the overall increased thrombotic risk [ 21 , 22 ]. Further understanding the hemostatic derangements that result in the prothrombotic state of surgical oncologic patients may allow for the development of targeted thrombophylactic measures focused on specific aspects of the hemostatic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…LY30 is helpful in diagnosing intraoperative coagulopathy due to disseminated intravascular coagulation (DIC) and can guide the administration of antifibrinolytics. It can also be used to help predict patients that are risk for developing venous thromboembolism, which is especially critical in oncologic populations that are prone to thrombotic events 15 …”
Section: Discussionmentioning
confidence: 99%
“…This information has led to the inclusion of viscoelastic testing in several transfusion guidelines 12–14 . Examples of VEA tests include thromboelastography (TEG®: Haemonetics Corporation), rotational thromboelastometry (ROTEM®: Instrumentation Laboratory), and the Quantra® System (Hemosonics, Quantra) 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global assays, such as thromboelastometry, may be more useful than conventional hemostatic laboratory tests in depicting the hypercoagulable state in oncologic and hematologic diseases [34]. Thorson et al demonstrated that intra-abdominal malignancies are associated with hypercoagulable ROTEM parameters including decreased CFT, increased alpha angle and increased MCF [35] while Davies et al noted that, compared to controls, patients with lung cancer have reduced CT, increased MCF and increased alpha angle [36].…”
Section: Discussionmentioning
confidence: 99%